Formulation and Evaluation of Fast Dissolving Tablets of Oxcarbazepine Using Liquisolid Technology - Mohana, Bindhu Booraguntae; Maddi, Eswar Gupta; Dang, Raman (Indian Journal of Pharmaceutical Education and Research, 2024)
Background/Aim The aim of the study was to improve the dissolution profiles of Oxcarbazepine (OXC) from its tablets. This study was done to evaluate the effects of different formulation variables, i.e. type of non-volatile liquid vehicles on oxcarbazepine dissolution rate from its tablets. Materials and Methods The liquisolid tablets were formulated with three different liquid vehicles, namely Polyethylene glycol 200, Propylene glycol and 20% Tween 80 aqueous solution. Micro-crystalline cellulose was used as a carrier material, silicon dioxide as a coating material and sodium starch glycolate as super disintegrate. The empirical method introduced by Spireas and Bolton (1999) was applied strictly to calculate the amounts of coating and carrier materials required to prepare fast dissolving tablets of OXC using liquisolid technique. The tablets passed all the routine quality control tests prescribed by official books. In vitro drug dissolution testing of the liquisolid tablets were done and compared with commercial tablets in 1% SLS solution as dissolution media as per USFDA. Results It was found that the dissolution rate of oxcarbazepine was highest from liquisolid tablets of oxcarbazepine formulated using PEG 200. Differential scanning calorimetry, PXRD and Fourier transform infrared evaluation of our best tablet Formulation (F2) indicated that there is no physico-chemical interaction between OXC and the excipients. Conclusion In vitro dissolution testing, DSC, PXRD and FTIR studies confirmed F2 as the best formulation with respect to drug dissolution rate and revealed that there is no incompatibility between the drug and excipients used in the formulation.
Keywords: Oxcarbazepine; Fast dissolving tablets; Liquisolid technique; Solubility; Dissolution rate